Variability of Sea Surface Temperature in Indonesia Based on Aqua Modis Satellite Data - Nurul Fatimah Yunita; Muhammad Zikra (IPTEK The Journal of Engineering, 2017)
Sea surface temperature (SST) is one of the oceanographic factor in seawater. Its value depends on several factors. In indonesia, SST value depend on season and location. The aims of this study are to analyze the spatial and temporal variability of SST using 10-years (2007-2016) Aqua Modis satellite data. The result shows that the average of SST in Indonesia ranges from 27 – 31 °C depending on location. SST in equator area range from 30 – 31 °C and in nonequator area range from 27 – 30 °C. Monthly and seasonal variation of SST also show different value for each area in the indonesian region.